FTIR – ATR aplicado à discriminação de microalgas planctônicas verdes cocóides - Moraes, Guilherme Pavan de (Universidade Federal de São Carlos, 2014)
This work proposes the use of the Fourier Transform Infrared (FTIR) spectroscopy as part of a polyphasic approach to assist the identification and classification of coccoid green microalgae. Attenuated Total Reflectance (ATR) technique was tested to determine if it can provide highly reproducible spectra, a primary requirement to achieve good discrimination between strains of microorganisms. It was also tested spectral window selection, in conjunction with spectra pre-treatments, to determine the best method to perform the strains discrimination. The results were evaluated by reproducibility of spectra and chemometrics analyses by principal components (PCA) and hierarchical clusters (HCA) analysis, in terms of correct discrimination and classification of closely related chlorophycean coccoid microalgae strains, compared to currently accepted classifications. ATR technique provided the reproducibility needed, verified by the excellent strains discrimination. Further, strains were positioned by HCA in clades correctly correlated to classification ranks orders and families. However, these results were obtained when using spectral windows that differ from previously reported studies, 1500 1200 cm-1 and 900 675 cm-1, excluding spectrum regions relative to storage compounds, which was found to negatively impact the analyses. It was concluded that the ATR - FTIR technique has great potential to assist traditional approaches of coccoid green microalgae identification and classification, though a careful spectrum region selection is needed.
Keywords: Ficologia; Chlorophyceae; Discriminação; Espectroscopia de infravermelho; Quimiometria; CIENCIAS BIOLOGICAS::ECOLOGIA